Control of the Orientation and Photoinduced Phase Transitions of Macrocyclic Azobenzene. Issue 51 (8th November 2013) - Uchida, Emi; Sakaki, Kouji; Nakamura, Yumiko; Azumi, Reiko; Hirai, Yuki; Akiyama, Haruhisa; Yoshida, Masaru; Norikane, Yasuo
Abstract Photoinduced phase transitions caused by photochromic reactions bring about a change in the state of matter at constant temperature. Herein, we report the photoinduced phase transitions of crystals of a photoresponsive macrocyclic compound bearing two azobenzene groups (1) at room temperature on irradiation with UV (365 nm) and visible (436 nm) light. The trans/trans isomer undergoes photoinduced phase transitions (crystal–isotropic phase–crystal) on UV light irradiation. The photochemically generated crystal exhibited reversible phase transitions between the crystal and the mesophase on UV and visible light irradiation. The molecular order of the randomly oriented crystals could be increased by irradiating with linearly polarized visible light, and the value of the order parameter was determined to be −0.84. Heating enhances the thermal cis‐to‐trans isomerization and subsequent cooling returned crystals of the trans/trans isomer.